For Which Patients Should Bladder Preservation Be Considered After a Complete Response to Neoadjuvant Chemotherapy - Laukhtina, Ekaterina; Quhal, Fahad; von Deimling, Markus; Kawada, Tatsushi; Yanagisawa, Takafumi; Rajwa, Pawel; Majdoub, Muhammad; Enikeev, Dmitry; Shariat, Shahrokh F (European urology focus, 2023)
Given the morbidity associated with radical cystectomy (RC) and the significant survival benefit for patients who experience tumor downstaging after neoadjuvant chemotherapy (NAC), there is growing interest in bladder preservation strategies for select patients who have a complete response (CR) to NAC. In this mini-review we discuss the concept of avoiding RC as an alternative option for patients who experience a clinical CR following NAC. Several studies support this concept, with comparable long-term survival outcomes observed for patients with cT0 disease after NAC and patients undergoing RC. However, the definitive approach and the optimal surveillance strategy for patients with a clinical CR who choose bladder preservation are lacking. A dynamic response-driven bladder preservation strategy is a highly anticipated option for patients and is needed to avoid debilitating overtreatment. PATIENT SUMMARY: For selected patients with bladder cancer who experience a complete response to chemotherapy before any surgery, close follow-up might be an alternative option to surgical removal of the bladder without compromising cancer control.
Keywords: cystektomie; nádory močového měchýře; lidé; Pathologic Complete Response; Neoadjuvant Therapy; Urinary Bladder Neoplasms; Humans; Cystectomy; neoadjuvantní terapie; močový měchýř; Urinary Bladder; patologická kompletní odpověď